The Lions Paw. - White, Robe (New York Scholastic, 1972)
Ben, Penny and Nick are running away. Searching for them are Bens uncle, the Coast Guard, everybody in Florida. Will they make good their escape? And will they find the Lions Paw?
Keywords: Literature